Factors Associated With Social Work Students' Academic Stress During the COVID-19 Pandemic: A National Survey. (18th August 2021) - Scheffert, Aynsley H. M.; Parrish, Danielle E.; Harris, Helen
ABSTRACT: The COVID-19 pandemic has impacted individuals across the world and disrupted societal systems, including educational institutions. The aim of the current cross-sectional survey of U.S. social work students was to describe: (1) students' experiences of COVID-19-related stress, academic stress, and access to supports; (2) changes in academic stress following the onset of the COVID-19 pandemic; and (3) factors that contributed to a change in academic stress following the onset of the COVID-19 pandemic. An independent samples t-test identified an increase in students' academic stress following the onset of the COVID-19 pandemic and multivariate regression determined factors contributing to levels of student stress, including program support and access to academic resources. Implications for social work programs' responses to disasters are discussed.